Adherence to Mediterranean Diet Offers an Additive Protection Over the Use of Statin Therapy: Results from the ATTICA Study (2002-2012) - B. Panagiotakos, Demosthenes; N. Georgousopoulou, Ekavi; A. Georgiopoulos, Georgios; Pitsavos, Christos; Chrysohoou, Christina; Skoumas, Ioannis; Ntertimani, Maria; Laskaris, Alexandros; Papadimitriou, Lampros; Tousoulis, Dimitrios; Stefanadis, Christodoulos; the ATTICA Study group (Current Vascular Pharmacology, 2015)
Background and Aims: The protective role of Mediterranean diet on cardiovascular disease (CVD) risk has been extensively discussed in the literature, but its incremental effect over the use of CVD risk reducing agents (such as hypolipidemic treatment) has rarely been evaluated. Methods: The ATTICA study was carried out in the Athens area during 2001-2002 and included 3042 participants free of CVD at baseline (49.8% men, aged 18-89 years). Adherence to Mediterranean diet was assessed using the MedDietScore (range 0-55) and statin use was recorded for all subjects. During 2011-2012, 2583 out of the 3042 baseline participants attended the 10-year follow-up of the ATTICA study (15% lost-to-follow-up) and CVD development was recorded. Results: Adherence to Mediterranean diet (highest tertile) decreased CVD risk by 29.3% (Hazard Ratio (HR): 0.707, 95% Confidence Intervals (CI): 0.537-0.831) as compared with the lowest tertile, independently of statin use. Patients with hyperlipidemia on a statin that adopted unhealthy dietary habits (lowest tertile) had 75% increased CVD risk than normolipidemic subjects with healthy dietary habits (HR=1.75, 95%CI: 1.33-2.29). The addition of Mediterranean diet tertiles in the multivariable model reclassified 46.7% of the participants to CVD risk categories. Conclusion: Adherence to Mediterranean diet confers a considerable reduction in CVD risk, independently of gender, age, family history of CVD, diabetes mellitus, smoking status, hypertension and physical activity status. Therefore, CVD prevention strategies should involve the implementation of a Mediterranean diet in both the general population and patients on a statin.
Keywords: mediterranean diet